Internal Curing Effects of Slag on Properties and Microstructure of Ambient-Cured Fly Ash-Based Geopolymer Mortar - Li Xiao; Chao Zhang; Hongen Zhang; Zhengwu Jiang (Buildings)
The preparation of ambient-cured fly ash-based geopolymer mortar (FAGM) with high strength by utilizing the high chemical reactivity of slag is key to realizing the sustainable and efficient application of solid waste resources. This paper investigates the influence of different type S95 slag contents (0%, 5%, 10%, 15%, 20%, 25%, and 30%) on the fluidity, setting time, and mechanical properties of FAGM at ambient temperature. The direct method is first adapted to monitor the influence of slag on geopolymerization. The results indicate that slag has a minimal effect on the fluidity of the mortar, while the setting time decreases and compressive strength increases with higher slag content. For FAGM with 30% slag content, the setting time is reduced from 3160 min to 140 min, with a decrease of 95.6%, and a 3-day and 28-day compressive strength increase from 1.5 MPa and 34.7 MPa to 33.5 MPa and 73.4 MPa, with enhancements of 2170.2% and 110.3%, respectively. Slag also exerts an internal curing effect, raising the internal curing temperature and accelerating the geopolymerization process of fly ash, thereby improving the compactness of FAGM and reducing its porosity. This approach successfully enables the production of high-strength, ambient-cured FAGM.